TVI and SIC news websites : public participation and editorial criteria - Lima, Helena Laura Dias de (2012)
Internet produced new forms of newsmaking and new technologies play now a central role in newsrooms. A great diversion of participation is now possible and news sites are used by the public to express opinions, debate the subjects of the agenda, and include their own material. Still, journalists’ attitude towards public participation tends to be framed by their perceptions of professional roles. Television has a tradition of public participation but it’s not clear if the TV sites mirror this practice, particularly in the news organization. This study is a first attempt to understand the relation between the news published and the publics’ participation. In order to establish that correlation, news were divided in sections: Politics, Economy, International, Society, and the public participation was measured according to the number of comments under each of them. The aim of this study is to try to indentify if there is a similar behavior by the TV news agenda and the public’s reaction. The sample will comprehend the study of the two TV news sites for a month period recorded daily at a given hour, and the published comments in the three following hours.